THE READINESS OF SECONDARY SCHOOL TEACHERS IN DEVELOPING LEARNING TOOLS FOR BLENDED LEARNING MODEL - Junarti Junarti; Puput Suriyah (Proceeding International Conference on Digital Education and Social Science, 2022)
This research aims to prepare teachers for the process of developing mathematical learning tools based on the blended learning model. In order to suit the needs of students in offline and online learning, mathematics learning tools evolved into blended learning model tools. Mixed-method concurrent embedded is the employed method in this study. Simultaneous collection of quantitative and qualitative data was also conducted in this study. The method known as ADDIE (Analysis, Design, Development, Implementation, and Evaluation) was utilized in developing the learning tools. 72% of the responses to the study on teacher readiness to design blended learning model learning materials were positive. According to the results of the learning tools' validity aspect, the material's content is appropriate, and its components are consistent. Furthermore, it demonstrates that the learning tools are user-friendly, curriculum-aligned, and implementable based on their actual use. Finally, based on efficacy, student learning test scores are above the minimum standard (75 on a scale of 100) with a success rate of 91.4%, indicating that classical mastery is reached. The result is that teachers are prepared to develop blended learning model learning tools, which can be applied in secondary schools to study mathematics.